Animal Cell Technology: Basic & Applied Aspects Proceedings of the Seventeenth Annual Meeting of the Japanese Association for Animal Cell Technology (JAACT), Nagoya, Japan, November 15-18, 2004 - Iijima, Shinji; Nishijima, Ken-ichi (Animal Cell Technology: Basic & Applied Aspects, 2006)
Animal cell technology is a growing discipline of cell biology which aims not only to understand structures, functions and behaviors of differentiated animal cells, but also to ascertain their abilities to be used in industrial and medical purposes. The goal of animal cell technology includes accomplishments of clonal expansion of differentiated cells with useful ability, optimization of their culture conditions, modulation of their ability for production of medically and pharmaceutically important proteins and the application of animal cells to gene therapy, artificial organs and functional foods. This book contains the proceedings of the 17th Annual and International Meeting of the Japanese Association for Animal Cell Technology (JAACT) that was held in Nagoya, Japan from November 15 to 18, 2004. This volume gives the readers a complete review of present state-of-the-art in Japan and other countries where this field is well advanced. The Proceedings will be useful for the cell biologists, biochemists, molecular biologists, immunologists, biochemical engineers and other disciplines related to animal cell culture, working in either academic environments or in industries of biotechnology and pharmacy.